Site-directed mutagenesis studies on a novel dual domain β-galactosidase/ β-glucosidase open reading frame identified from a dairy run-off metagenome - Ehrenreich, Craig Leigh (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScAgric)--Stellenbosch University, 2021.